ANALISIS NILAI-NILAI DALAM AJARAN KONFUSIANISME DALAM NOVEL SAN GUO YAN YI DAN RELEVANSINYA TERHADAP PENDIDIKAN KARAKTER - Adnan. AR, Muh. Darul; Usman, Misnawaty; Mustarih, Nirdayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the Confucian values contained in San Guo Yan Yi, their representation through characters and events, and their relevance to character education. This study employed a qualitative approach using the content analysis method. The data source was San Guo Yan Yi by Luo Guanzhong, translated by Leo Junaedi. The findings reveal that the novel represents five core Confucian values, namely Ren (仁), Yi (义), Li (礼), Zhi (智), and Xin (信), which are reflected through the characters' actions, dialogues, decisions, and interpersonal relationships. These values are represented by the characters Liu Bei, Guan Yu, Zhao Yun, Zhuge Liang, Cao Cao, Zhang Liao, Sun Quan, Zhou Yu, and Lu Bu. Furthermore, the study indicates that the Confucian values portrayed in the novel are relevant to character education, as they provide moral lessons related to ethics, leadership, responsibility, wisdom, and loyalty. Therefore, San Guo Yan Yi has the potential to be utilized as a learning resource to support the strengthening of character education in Mandarin language learning.